Book Classification System Based on Dewey Decimal Classification by Multinomial Naïve Bayes Method - Mulyani, Esti; Bunga, Munengsih Sari; Ishlakhuddin, Fauzan; Kastuti, Kastuti (Jurnal Sistem Informasi Bisnis, 2025)
Libraries have the main task of processing library materials by classifying books according to certain methods. Dewey Decimal Classification (DDC) is the most widely used method in the world to determine book classification in libraries. However, the classification process using DDC is inefficient because it takes a long time for the large number of books in the library. This is a serious problem experienced by all libraries, so a solution is needed to bridge the problem. automatic classification system can be the right alternative to overcome the problem. In this research, an automatic classification system based on DDC using the Multinomial Naive Bayes Method so that it can speed up the classification process. This system was created using the CodeIgniter framework with the PHP programming language and MariaDB. Test results from 100 training data and 30 test data show that there are 24 test data with correct classification results and 6 test data with incorrect classification results. So it can be concluded that the accuracy rate of the test is 80%.